Global context of the Nigerian public service reform since 1945 - Dauda, Bola (1996)
This paper reviews the reforms of the Nigerian civil service in the context of the three areas (a) country or regional case study as a basis for comparative evaluations of public service reforms; (b) professional identity under reform; and (c) ethical issues in the reform of public sectors, and concentrates on what determines the professional identity of civil servants and how success or otherwise of reform are determined by the public perception of the self-perceived professional identity of the civil service itself. It concludes with the ethical issues in the reform of public sector. - Reproduced
Keywords: Civil service reform - Nigeria; Civil service - Nigeria; Administrative Reform